Pertumbuhan dan Hasil Kubis Bunga (Brassica oleraceae var. Botrytis L.) pada Media Tanam Kompos Gulma Air - Susilawati Susilawati; Muhammad Ammar; Z. D Asmara (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Susilawati et al, 2017. The Growth and Yield of Cauliflowers (Brassica oleraceae var. Botrytis L.) on Planted Media of Aquatic Weeds Compost. JLSO 6(1):43-48.The objective of this research was to know the growth and yield of cauliflowers on various planted media organic of compost aquatic weeds. This research was conducted from November 2016 to Febuary 2017. The research was rendomized block design with ten treatments and three replications. Each unit consisted of 3 plants, so there were 90 plants. The treatments were B0: (soil 100%), Be1 (75% soil: 25% water hyacinth fertilizer), Be2 (50% soil: 50% water hyacinth fertilizer), Be3 (25% soil: 75% water hyacinth fertilizer), Bu1 (75% soil: 25% hymenachne compost), Bu2 (50% soil: 50% hymenachne compost), Bu3 (25% soil: 75% hymenachne compost), Bi1 (75% soil: 25% salvinia compost), Bi2 (50% soil: 50% salvinia compost), Bi3 (25% soil: 75% salvinia compost). The result showed that the treatment 75% soil and 25% salvinia compost gave the best effects on weight flowers, leaf number, weight of fresh roots and weight of dry roots.